Skin Edema in First Trimester Fetuses - Jenewein, N.; Christ, J.; Günther, D.; Hutsteiner, P.; Ortmann, O.; Germer, U. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
Purpose: The aim of this study was to prove an association between generalized skin edema and nuchal translucency (NT) thickness and its predictive value for aneuploidy and structural anomalies. Materials and Methods: In this retrospective study fetuses with and without skin edema in the first trimester with an NT above 2.2 mm were compared. Statistical significance was calculated with the Chi-square test (p < 0.05). Results: 237 fetuses were included in this study (median NT of 3.0; IQR: 2.5 – 3.9 mm, median CRL 68.8; IQR: 58.9 – 74.9 mm). 17.3 % presented with skin edema. The rate of skin edema was 1.3 % in the group with an NT < 95th percentile, 2.7 % in the group with an NT between the 95th and 99th percentile, 17.5 % with an NT of 3.5 – 4.4 mm, 36.4 % with an NT of 4.5 – 5.4 mm, 54.5 % with an NT of 5.5 – 6.4 mm and 95.5 % with an NT above 6.5 mm. 19 % had chromosomal disorders. The rate of aneuploidy was 61.0 % (25/41) in the group with skin edema which was significantly higher than the rate of 10.2 % (20/196) in those without skin edema (p < 0.0001). 12 % had structural anomalies in euploid fetuses. The rate of anomalies was 43.8 % (7/16) in the group with skin edema and significantly higher compared to 9.1 % (16/176) in those without skin edema (p < 0.0005). Conclusion: Our data show a clear association between the thickness of NT and the rate of skin edema. Skin edema has a high predictive value for aneuploidy or structural malformations. Therefore, fetuses with skin edema should have early malformation scans in case of normal karyotype.
Keywords: ultrasound; first trimester; skin edema